Efeitos da incorporação de nanotubos de haloisita carregados com clorexidina na atividade antimicrobiana e em propriedades físicas de uma resina acrílica para reembasamento de próteses dentárias - Oliveira, Mayara Soares Cardoso Sales (2023)
The creation of a dental reline enhanced with nanoparticles, such as Haloisite nanotubes (HNT), carrying antimicrobials, such as chlorhexidine (CHX), may be relevant in the control and treatment of lesions associated with the use of removable dental prostheses. Therefore, was evaluated the effect of incorporating CHX-loaded HNTs (HNT/CHX) on antimicrobial activity and physical properties of a reline material (RE). HNTs were loaded with CHX at 20% and the incorporation efficiency calculated. The obtained HNT/CHX was characterized by ultraviolet visible spectroscopy (UV/VIS), scanning electron microscopy (SEM), infrared spectroscopy and thermogravimetric analysis. A total of 72 specimens of a resilient RE of self-curing acrylic resin with 0, 3%, 5% or 10% HNT/CHX were obtained. The release of CHX from the RE was measured by UV/VIS after 4, 8 hours, 1, 2, 5, 10, 20, 30, 40 and 50 days. The antimicrobial effect against Candida albicans and Staphylococcus aureus was evaluated in disc-diffusion agar test. After obtaining the specimens (T0) and 30 days of immersion in distilled water (T1), surface roughness (Ra), color variation (ΔE) and surface topography of the material were evaluated. Data were analyzed using 1- and 2-factor ANOVA with Bonferroni post-test, and paired t-test (α = 0,05). The incorporation efficiency of CHX into HNT was 8.15%. In aqueous medium, the nanocomposite showed gradual and increasing release of CHX, with the highest peak in the first 24 hours (6.25%), reaching the concentration of 10% at the 50-day evaluation. A significant (p<0.001) and dose-dependent antimicrobial effect was observed in both periods against C. albicans, with the best result at 10%. For S. aureus, the HNT/CHX groups showed significant antimicrobial action (p<0.001) and similar to each other. At T0, all the test groups showed similar Ra (p=0.588); on the other hand, at T1 the 5% and 10% groups showed significant increase in Ra (p<0.001), with greater variation observed in the 10% group (p=0.001). ΔE in the groups containing HNT/CHX was similar at T0 (p=0.578) and T1 (p=0.189). Intragroup ΔE was statistically lower in the 10% group (p<0.001). It is concluded that incorporation of HNT/CHX in RE at low concentrations, as in the 3% group, may confer sustained antimicrobial characteristic, presenting the potential to act in the control and treatment of lesions associated with the use of dental prostheses, without significantly impairing the evaluated properties of the relining material.